2015
DOI: 10.1111/bjep.12102
|View full text |Cite
|
Sign up to set email alerts
|

Language‐related values, reading amount, and reading comprehension in students with migration backgrounds

Abstract: The new evidence is of practical relevance for teachers, educational scientists, and psychologists who are striving to improve the educational outcomes of bilingual students. Further research needs and the significance of the results for educational practice and home environment are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Participants that believe this link to be stronger may engage in more reading, resulting in higher reading performance. This relationship has also been demonstrated by El-Khechen, Ferdinand, Steinmayr, and McElvany (2016), who found that the utility value placed on German by German-Turkish bilinguals predicted German reading competency. As such, the contribution of this study to theoretical frameworks is the extension of these frameworks to reading-specific research.…”
Section: Discussionsupporting
confidence: 53%
“…Participants that believe this link to be stronger may engage in more reading, resulting in higher reading performance. This relationship has also been demonstrated by El-Khechen, Ferdinand, Steinmayr, and McElvany (2016), who found that the utility value placed on German by German-Turkish bilinguals predicted German reading competency. As such, the contribution of this study to theoretical frameworks is the extension of these frameworks to reading-specific research.…”
Section: Discussionsupporting
confidence: 53%
“….43]). It seems that the broad confidence intervals resulted from studies with smaller sample size (e.g., El-Khechen et al, 2016). One effect of one study (Villiger et al, 2014) showed a confidence interval that included zero indicating a non-significant effect.…”
Section: Meta-analytic Resultsmentioning
confidence: 99%
“…In the reading domain, studies examining the relations among motivational, behavioural, and performance variables are more common (e.g., De Naeghel, Keer, Vansteenkiste, & Rosseel, 2012; El‐Khechen, Ferdinand, Steinmayr, & McElvany, 2016; Troyer, Kim, Hale, Wantchekon, & Armstrong, 2019) than in writing research. Across these studies, authors typically placed reading frequency as a mediator of the motivation–performance relationship.…”
Section: Introductionmentioning
confidence: 99%